The Impact of Islamic Tolerance Awareness on Perceived Academic and Societal Tolerance: An Investigation Among University Students in the UAE - Mostafa, Imad Ibraheem; Kaba, Abdoulaye (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2026)
This study examined the impact of Islamic tolerance awareness on perceived academic and societal tolerance among university students in the United Arab Emirates. The study consisted of 422 participants representing diverse genders, age groups, academic levels, and specializations. Findings of the study reveal a high level of Islamic tolerance awareness among the participants, with no statisticalsignificant demographic differences. While societal tolerance perceptions were largely equal across demographics, gender-based differences emerged in academic tolerance, with male students reported higher perceptions than females. Correlational analyses demonstrated strong interrelationships between tolerance awareness, academic tolerance, and societal tolerance, while regression results confirmed that awareness significantly enhances students perceptions towards academic and social tolerances.